PENGEMBANGAN MATERI PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA INGGRIS DI SMP - Agusliana, Agusliana; Rachmawati, Rachmawati; Hardjono, Hary Soedarto (Program Magister Teknologi Pendidikan Universitas Jambi, 2014)
This study intends to describe the process of developing learning materials for Junior High School students, especially transactional utterancess through videos, and to provide media for teaching speaking. This development was necessarily done due to the fact that students’ speaking ability was still poor. This was caused by the lack of media which could support the students in dealing with the issue. Therefore, an development of learning materials of English speaking skills was needed in order to reach an effective and innovative goal. This study follow these five stages. The stages are need anlysis, designing product, production, validation, try out and packing the product. The result of evaluation from the media expert is 81,3%, and subject matter is 84,4%. Based on the small group try out that is done to ten students are 81,4%, while the big group try out that is done to twenty students are 87,5%. There `s an increasing of students` speaking ability that`s shown by the test. The increasing is about 17,55% at small group try out and 22,25% at the big group try out. So It can be said that the product is proper as a media in teaching speaking. In the other hand the use of this English development product in teaching speaking can increase student`s speaking ability. Keyword: development, learning material, speaking skill.